PEMERIKSAAN PENDERITA PRESBYOPIA DENGAN STATUS REFRAKSI HYPERMETROPIA, MYOPIA, ASTIGMAT DAN EMETROPIA MASYARAKAT CILANDAK PERIODE JANUARI 2023 - BUNYAMIN RIZKI ABDILLAH; Opep Cahya Nugraha; Hanie Supandi (Akademi Refraksi Optisi dan Optometry Gapopin, 2023)
The inability of a person to see close objects clearly can occur for several reasons, including presbyopia. Meanwhile, a person's inability to see distant objects clearly can occur for several reasons, including because his eyes have hypermetropic refractive status, myopia, astigmatism and emmetropia. This research was carried out using a descriptive method through a quantitative approach. The results showed that of the 53 Cilandak people who received a subjective refraction examination with optic 688, they were presbyopic patients with right (26.4%) and left (28.3%) hypermetropia refractive status, right and left myopia (41.5%), left com astigmatism (22.6%), right com astigmatism (18.9%), right sim astigmatism (13.2%), left sim astigmatism (15.1%), and right emmetropia (31.1%) and Emmetropia left 28.3%). In the examination of subjective refraction, determining the size of spectacle lenses for far vision for patients with hypermetropia is based on a concept, namely by providing the largest spherical lens that can produce the best vision. Meanwhile, for myopia, the weakest spherical correction lens is provided. For astigmatism, cylindrical correction lenses are given, determining the size of spectacle lenses for near vision for presbyopia sufferers with hypermetropia refractive status, which is the accumulation of lens diopters for far vision and addition. It can be concluded that the ultimate goal of examining subjective refraction in patients with presbyopia with hypermetropia, myopia and astigmatism is to determine the appropriate lens size, so that glasses made with these sizes can function as a visual aid.